EKSTRAK JAHE (Zingiber officinale Roscoe) PENGHAMBAT OKSIDASI LDL [Ginger (Zingiber officinale Roscoe) Extracts Inhibits LDL Oxidation] - Aisyah Tri Septiana; Fransiska R Zakaria; Sulistiyani , (Jurnal Teknologi dan Industri Pangan, 2002)
Oxidative modification of LDL is believed to play an important role in atherogenesis.  Dichloromethane extract of ginger rhizomes exhibited a strong antioxidative activity using linoleic acid as substrate.  We investigated the in vitro effect of these extract enrichment on the prevention of oxidative LDL by CuSO4. Plasma was supplemented with 43, 430, or 4300 mg/ml dichloromethane extract in dimethylsulfoxide (DMSO) (10 ml DMSO per ml plasma), incubated, and the LDL was isolated.  Lag phase and malonaldehide content was analized after the isolated LDL was oxidized using CuSO4.  The result showed that dichloromethane extract of ginger rhizomes suplementation prolonged lag phase and reduced malonaldehide formation depended on its concentration.  Concentration of 43 and 4300 mg/ml plasma of these extract reduced malonaldehide formation by 35,29 % and 69,72 % respectively, but not significant in prolonged lag phase.  Concentration of these extract with largest prolonged lag phase (82,16 %) and reduced malonaldehide formation (74,95 %)  was 430  mg/ml plasma.  This research has shown that ginger extract is capable of protecting LDL from oxidation.